Strategi Pengadaan Bahan Non Buku Di Perpustakaan Universitas Negeri Padang Pada Era Revolusi 4.0 - Aulia, Atikah; Ayudian Putri, Rahma Diani; Tri Andini, Titin; Rahmah, Elva (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2020)
This study aims to determine the strategy of procurement of non-book material in the central library of the state university of padang that can raise procurement and constraints in implementing strategies in the revolutionary era 4.0. this type of research is a qualitative approach with a method of interviewing the head of the padang state university library and staff management staff, library research by collecting data from reference materials, archives, and documents related to this research. The result of this study are the fact that in the central library of the state university of padang procurement of non-book material is no longer used because of the lack of a place for non-book material media such as tools, so people search for and obtain material or material on the internet that occurred in the revolutionary era 4.0.